„Ona nie była jedną z nas”. Wokół „feminizmu” Hannah Arendt - Barańska, Edyta (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Feminists have a problem as they create themselves that which they fight against. On the one hand they demand that they are perceived through the perspective of femininity and they want to emphasize this femininity. On the other hand, though, they fight against a stereotypical feminine image. Arendt is different – she does not distinguish women because of their gender. In this sense Arendt is neither a feminist nor an ant-feminist. She does not touch upon the issue of gender at all. She does not claim that a woman lives at home whereas a man lives in the world, in the public space. Yet she does claim that the space of the household is the realm of necessity while the public space – that of freedom. In Arendt’s opinion in the public space are operating people rather than men or women. Mary Dietz is therefore right in saying that gender loses significance at the operational level. This concerns both genders. In Arendt’s theory there exists a single category – that of a citizen. Acitizen has no gender at all. He or she can be a man or woman at home, and not in public. Therefore Arendt cannot be said to be a feminist or an anti-feminist. She falls beyond these categories as what counts for her is participation in politics, not gender.